Systems thinking for planning and evaluating conservation interventions. Issue 7 (29th April 2019) - Mahajan, Shauna L.; Glew, Louise; Rieder, Erica; Ahmadia, Gabby; Darling, Emily; Fox, Helen E.; Mascia, Michael B.; McKinnon, Madeleine
Abstract: As conservation shifts to meet the challenges of our globalized world, approaches for planning and evaluating interventions must evolve to account for the increasing complexity of conservation problems and the dynamic, multiscalar relationships between humans and the environment. Systems thinking offers approaches that could help conservation be more adaptive, transparent, and evidence‐based. Using case studies and the literature, we trace the evolution of systems thinking and demonstrate how systems mapping could support the process of planning and evaluating interventions. Systems mapping helps disentangle the context of conservation and encourage collaborative planning that integrates diverse views. It can also change the way interventions are characterized and communicated by emphasizing the systems targeted for change as opposed to actions. Last, it can encourage evidence‐based decision‐making by identifying indicators attune to complexity, prompting discussion on knowledge gaps, and filling gaps through qualitative mapping or computational modeling. Integrating systems thinking in practice will help practitioners foster the capacity for learning and adaptation required for conservation to deliver global results.